2013
DOI: 10.1128/jb.00990-13
|View full text |Cite
|
Sign up to set email alerts
|

ExsA and LcrF Recognize Similar Consensus Binding Sites, but Differences in Their Oligomeric State Influence Interactions with Promoter DNA

Abstract: bExsA activates type III secretion system (T3SS) gene expression in Pseudomonas aeruginosa and is a member of the AraC family of transcriptional regulators. AraC proteins contain two helix-turn-helix (HTH) DNA binding motifs. One helix from each HTH motif inserts into the major groove of the DNA to make base-specific contacts with the promoter region. The amino acids that comprise the HTH motifs of ExsA are nearly identical to those in LcrF/VirF, the activators of T3SS gene expression in the pathogenic yersini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…Based on the defect exhibited by ExsA L140A,L148A , the corresponding mutations recently were introduced into Yersinia pestis LcrF, a close homolog of ExsA that exists as a dimer. As expected, the LcrF L136A,L144A mutant is largely monomeric, preferentially binds to a single site in electrophoretic mobility shift assays, and is significantly impaired for T3SS promoter activation (32).…”
Section: Discussionmentioning
confidence: 88%
“…Based on the defect exhibited by ExsA L140A,L148A , the corresponding mutations recently were introduced into Yersinia pestis LcrF, a close homolog of ExsA that exists as a dimer. As expected, the LcrF L136A,L144A mutant is largely monomeric, preferentially binds to a single site in electrophoretic mobility shift assays, and is significantly impaired for T3SS promoter activation (32).…”
Section: Discussionmentioning
confidence: 88%
“…However, these proposed LcrF binding sites were highly variable in terms of distance from the transcriptional start site, directionality, and distance of the half-sites from each other (17). In a more recent analysis, King et al observed that the carboxy-terminal domain of LcrF is nearly identical to the DNA binding region of the homologous AraC-like master regulator ExsA of the Pseudomonas aeruginosa T3SS (18). The authors further showed that Y. pestis LcrF binds and activates ExsA-dependent promoters in P. aeruginosa.…”
Section: Lcrf History Structure and Functionmentioning
confidence: 98%
“…The authors further showed that Y. pestis LcrF binds and activates ExsA-dependent promoters in P. aeruginosa. Similarly, ExsA was able to induce expression of T3SS genes in Y. pestis in the absence of LcrF (18). LcrF and ExsA were shown to interact with a common nucleotide sequence motif (AaAAAnwnMygrCynnnmYTGyaAk), which is also recognized by activators of T3SS genes from Photorhabdus luminescens, Aeromonas hydrophilus, and Vibrio parahaemolyticus (W stands for A or T, M for A or C, Y for C or T, R for A or G, and K for G or T [with uppercase letters representing more highly conserved residues]) (18,21,22).…”
Section: Lcrf History Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…We took advantage of the fact that ExsA orthologs from Aeromonas hydrophila (AxsA), Photorhabdus luminescens (PxsA), Yersinia pestis (LcrF), and Vibrio parahaemolyticus (ExsA Vp ) each complement an exsA mutant for P exsD-lacZ reporter activity (60,61). Although these proteins are highly conserved in their C-terminal DNA-binding domains, their DNA sequences are less conserved ranging from 67 to 75% sequence identity relative to exsA.…”
Section: Figmentioning
confidence: 99%